Expanding food democracy: a perspective from the United States - Anderson, Molly D. (Frontiers in Sustainable Food Systems, 2023)
Food democracy can be a tool to combat capitalist hegemony in the food system and increase citizen’s knowledge about alternatives to obtaining food from concentrated food businesses. But for food democracy to further democratic goals, it needs to help create these alternatives as transformational spaces, seek genuine inclusion of underprivileged people in food system governance, and ensure that public forums for deliberation about the food system are active and respected by public institutions.